Security Analysis of LP3M Assignment Letter Management System Using OWASP ZAP at ITB NOBEL Indonesia - Nurul Istiqamah; Aulyah Zakilah Ifani; Eka Wijaya Paula; Zalfa Naqiyah (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
The LP3M Assignment Letter Management System is a forum for the academic community to submit letters such as resource person assignment letters, research, and also service. This system was created to make it easier for users to submit letters, because previously it was only manual. The LP3M assignment letter management system plays an important role in the process of managing, storing, and providing information related to lecturers' assignment letters at the Nobel Institute of Technology and Business Indonesia. The information stored on this website is sensitive and requires adequate protection. Therefore, the security analysis of the LP3M assignment letter website is a very important thing to do to ensure confidentiality, integrity, and data availability. The large number of users accessing allows one to steal personal data from users. So this research aims to analyze the security of the system using OWASP ZAP. There are 9 vulnerabilities detected in the LP3M mail management system. The test results on the system were obtained high 0, medium 64, low 176. The total number of security vulnerabilities found amounted to 240.